2015
DOI: 10.1037/cou0000071
|View full text |Cite
|
Sign up to set email alerts
|

Mediators between self-criticism and depression: Fear of compassion, self-compassion, and importance to others.

Abstract: This study was an investigation of the relationships between internalized self-criticism and depression and between comparative self-criticism and depression as these relationships are mediated by the fear of self-compassion, fear of compassion from others, self-compassion, and the perception that one is important to others. To examine these relationships, data were gathered via online survey methods from 206 university students at a large public Midwestern university in the United States. The Self-Criticism/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 50 publications
8
51
0
3
Order By: Relevance
“…One anticipated finding was that an increase of fear of compassion positive emotions predicts an increase of Callous-unemotional traits. This result shows promising similarities with contemporary literature as individuals in this population has tendencies of higher depression traits and low selfesteem that is also high in individuals with fear of compassion positive emotions [36,41,69]. With that, it may lead to dissociation of needs for positive responses and thoughts [68,70].…”
Section: Discussionsupporting
confidence: 78%
“…One anticipated finding was that an increase of fear of compassion positive emotions predicts an increase of Callous-unemotional traits. This result shows promising similarities with contemporary literature as individuals in this population has tendencies of higher depression traits and low selfesteem that is also high in individuals with fear of compassion positive emotions [36,41,69]. With that, it may lead to dissociation of needs for positive responses and thoughts [68,70].…”
Section: Discussionsupporting
confidence: 78%
“…However, conflicting evidence exists. Two studies found that self‐compassion strongly negatively correlated with FSC: whereas one is limited by using the full‐scale SCS (Joeng & Turner, ), one used only positive SCS (Gilbert, McEwan, Catarino, & Baião, ). The contradictory results are explicable by our proposal that the FSC scale appears to combine multiple fears/inhibitors, some representing threat system hyperactivity like conditioned fear of affiliative emotions or fear of connecting to deep loneliness, and others representing soothing system hypoactivity like a lack of models of compassion to draw from (see Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on the experiences of clients with depression, due to the significant role of self‐criticism on the development and maintenance of depression (Ehret, Joormann, & Berking, ). In contrast, self‐compassion has been found to be negatively related to depression and self‐criticism (Ehret, et al, ; Joeng & Turner, ). Therefore, an intervention that has the potential to increase self‐compassion, whilst reducing self‐criticism, holds particular promise for the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%